Quantum chemical calculations of the excited states of porphyrins - Suess, C.J. (2018)
The development of optical multidimensional spectroscopic techniques has opened up new possibilities for the study of biological processes. Ultrafast two-dimensional ultraviolet spectroscopy experiments have determined the rates of tryptophan → heme electron transfer and excitation energy transfer for the two tryptophan residues in myoglobin. Here we show that accurate prediction of these rates can be achieved using Marcus theory in conjunction with time dependent density functional theory (TDDFT). Key intermediate residues between the donor and acceptor are identified, and in particular the residues Val68 and Ile75 play a critical role in calculations of the electron coupling matrix elements. Our calculations demonstrate how small changes in structure can have a large effect on the rates, and show that the different rates of electron transfer are dictated by the distance between the heme and tryptophan residues, while for excitation energy transfer the orientation of the tryptophan residues relative to the heme is important.